Improvement of the solar efficiency of polymer solar cells by using 1, 3, 5-trichlorobenzene as Co-solvent - Kruefu V. (2014)
Bulk-heterojunction (BHJ) solar cells utilizing P3HT:PCBM composite using 2.5, 3.5, 5.5 and 7.5mg of 1, 3, 5-trichlorobenzene (TCB) as co-solvent were fabricated. The co-solvent method can induce a good quality of P3HT:PCBM thin film nanostructure, leading to enhanced absorption. With the optimized TCB quantity, the power conversion efficiency (PCE) achieved with the solar cell was up to 15% better than that attained by a similar device without the presence of TCB. The devices load with and without Niobium doped ZnO Nanoparticles (Nb/ZnO NPs) produced by flame spray pyrolysis (FSP) were also compared. © 2012 Taylor & Francis Group, LLC.